New reports of decapod Portunus monspeliensis A. Milne Edwards, 1860 from Miocene beds of eastern Slovenia with notes on palaeoecology and palaeobiogeography - Gašparič, Rok; Ossó, Àlex (Geologija, 2016)
In the present paper we report on several new occurrences of decapod Portunus monspeliensis A. Milne Edwards, 1860 from Miocene beds of eastern Slovenia, i. e. from the already known locality Šentilj in the northeastern Štajerska region and additional new localities in the Kozjansko and Dolenjska regions. These new reported occurrences of P. monspeliensis from the Middle Miocene (Badenian) strata of eastern Slovenia improve our knowledge of this otherwise widespread decapod crustacean. Additionally, we also re-evaluate the environmental preferences of the species and its wider palaeobiogeographical distribution during the Miocene in the Mediterranean, Atlantic and Paratethys Seas.